From the Last Mile to the Next Mile – 2022 Vietnam Poverty & Equity Assessment - World Bank (Washington, DC, 2022)
Vietnam is a country on the move and in transition. Indicators are pointing in the right direction, with many positive economic and social developments. The amount of progress that Vietnam has achieved in less than half a century since emerging from a war has been nearly without parallel. At the same time, Vietnam is a lower-middle-income country facing a challenging and uncharted road ahead to reaching upper-middle and high-income country levels in a shifting global economic and climatic landscape. In less than half a century since the end of the Vietnam War and thirty-five years since the Doi Moi reforms, Vietnam has become a vibrant economy and a sought-after market to the outside world. At the same time, despite remarkable progress, poverty remains a key concern among the population. Concerns over poverty amid high economic growth are not inconsistent; together they illustrate an absolute and inclusive rise in living standards, but also a population that seeks economic security and aspires for more. This Vietnam poverty and equity assessment is organized into two parts motivated by addressing both Last Mile and Next Mile issues: Part I reviews poverty and inequality trends over the last decade, 2010–2020; and Part II assesses opportunities for and challenges to Vietnam’s path to achieving its Next Mile aspirations and creating greater prosperity for households and workers.